2017
DOI: 10.1038/s41598-017-04241-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Plasmodium falciparum populations selected on the human endothelial receptors P-selectin, E-selectin, CD9 and CD151

Abstract: The ability of the parasite Plasmodium falciparum to evade the immune system and be sequestered within human small blood vessels is responsible for severe forms of malaria. The sequestration depends on the interaction between human endothelial receptors and P. falciparum erythrocyte membrane protein 1 (PfEMP1) exposed on the surface of the infected erythrocytes (IEs). In this study, the transcriptomes of parasite populations enriched for parasites that bind to human P-selectin, E-selectin, CD9 and CD151 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…That we did not find significant differences in receptor usage between the UM and CM isolates could be explained by the infection consisting of multiple P. falciparum genotypes, including those underlying var gene expression (Montgomery et al, 2006(Montgomery et al, , 2007. It is clear that HBMEC binding of some isolates is not affected by inhibition with aICAM-1 and rEPCR, indicating that other receptors may play a role in cytoadherence to brain endothelium, a phenomenon also seen with selected laboratory strains (Yipp et al, 2007;Avril et al, 2016;Mahamar et al, 2017;Metwally et al, 2017). Lately, dual receptor binding by one PfEMP1 variant has been reported, with some PfEMP1 being able to bind both EPCR and ICAM or CD36 and ICAM-1 simultaneously Lennartz et al, 2017).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…That we did not find significant differences in receptor usage between the UM and CM isolates could be explained by the infection consisting of multiple P. falciparum genotypes, including those underlying var gene expression (Montgomery et al, 2006(Montgomery et al, , 2007. It is clear that HBMEC binding of some isolates is not affected by inhibition with aICAM-1 and rEPCR, indicating that other receptors may play a role in cytoadherence to brain endothelium, a phenomenon also seen with selected laboratory strains (Yipp et al, 2007;Avril et al, 2016;Mahamar et al, 2017;Metwally et al, 2017). Lately, dual receptor binding by one PfEMP1 variant has been reported, with some PfEMP1 being able to bind both EPCR and ICAM or CD36 and ICAM-1 simultaneously Lennartz et al, 2017).…”
Section: Discussionmentioning
confidence: 60%
“…We also determined binding of the patient isolates to HBMEC and HDMEC in the presence of aICAM-1 antibody and rEPCR combined, but the limited data (Appendix Fig S3) showed no significant difference between UM and CM isolates, nor between HBMEC and HDMEC binding. It is clear that HBMEC binding of some isolates is not affected by inhibition with aICAM-1 and rEPCR, indicating that other receptors may play a role in cytoadherence to brain endothelium, a phenomenon also seen with selected laboratory strains (Yipp et al, 2007;Avril et al, 2016;Mahamar et al, 2017;Metwally et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Finally, adherent IEs are counted manually. These experiments demonstrated that laboratory-adapted trophozoite-stage IT4 and 3D7 isolates show different binding capacities to various ECRs under static conditions 31,33 . The main objective of this study was to characterize the binding behavior of erythrocytes infected with P. falciparum to the ECRs CD36, ICAM-1, P-selectin, CD9, and CSA under controlled flow and temperature conditions.…”
Section: Resultsmentioning
confidence: 85%
“…Endothelial cytoadhesion and the binding capacities of various laboratory strains and patient isolates of P. falciparum have been mainly investigated under static conditions 6,31,32 . This is classically achieved by directly incubating IEs with cells or recombinant receptors of interest 8,16,33,34 . Finally, adherent IEs are counted manually.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation